Experiences of primary health care practitioners dealing with emergencies - 'We are on our own' - Meghan Botes; Richard Cooke; Judith Bruce (AOSIS, 2023)
Background: Primary health care (PHC) focuses on health promotion and disease prevention; however, acute episodes and emergencies still occur at this level of care. The World Health Organization (WHO) proposes strengthening emergency care at a PHC level as a way of lessening the burden of disease on the overall health system. It is not known how health care practitioners at the PHC level experience management of emergencies. Aim: To explore and describe the experiences of PHC practitioners dealing with emergencies at PHC facilities in Gauteng, South Africa. Setting: The study was conducted in the District Health Services of Gauteng province in South Africa, including clinics, community health care centres and district hospitals. Methods: Using a qualitative approach, semi-structured interviews were conducted with a purposively selected sample of professional nurses and doctors from various levels of the district health care system. Data were transcribed and analysed using qualitative thematic analysis. Results: Various themes were identified related to the individual confidence and competence of the PHC practitioner, the team approach, the process of role and task allocation and the need for training. Conclusion: The study provided a voice for the needs of health care practitioners dealing with emergencies at the PHC level. The designing of a targeted and contextually appropriate approach to emergency care training of health care practitioners in the PHC setting that improves team dynamics and team performance, is recommended. Contribution: The insights of PHC practitioners dealing with emergencies contribute contextual relevance to any strategic improvement of care at this level.